2022
DOI: 10.3389/fimmu.2022.914799
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Actions of CD73 During Development and Suppressive Actions of Regulatory T Cells

Abstract: Adenosine (Ado) has been shown to have immunosuppressive effects in a variety of diseases. It can either be released directly into the extracellular environment by cells, or it can be produced by degradation of ATP within the extracellular spaces. This extracellular pathway is facilitated by the concerted actions of the ectoenzymes CD39 and CD73. In a first step CD39 dephosphorylates ATP to ADP and AMP, respectively, and in a second step CD73 converts AMP to Ado. Thus, activity of CD73 on the cell surface of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…A high molecular concentration of Bic seems unnecessary and even counterproductive, as we also observed for Bic05 and Treg differentiation ( Figure 3C ). For Bic05, induced Tregs were both IL-10 + and Foxp3 + and expressed more CD73 than zym-induced Tregs, which suggests the participation of purinergic signals ( 51 , 52 ). Finally, both Bics seemed able to confer regulatory properties to PBMC populations with the development of particular Tregs.…”
Section: Discussionmentioning
confidence: 94%
“…A high molecular concentration of Bic seems unnecessary and even counterproductive, as we also observed for Bic05 and Treg differentiation ( Figure 3C ). For Bic05, induced Tregs were both IL-10 + and Foxp3 + and expressed more CD73 than zym-induced Tregs, which suggests the participation of purinergic signals ( 51 , 52 ). Finally, both Bics seemed able to confer regulatory properties to PBMC populations with the development of particular Tregs.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have indicated that elevated levels of CD73 are often associated with an increase in immunosuppressive cell populations such as Tregs, MDSCs, and tumor-associated macrophages (TAMs) ( 32 , 33 ). To analyze the affect of OTUD4 in modulating tumor immunity, we examined the tumor immune infiltrates using a high-dimensional spectral flow cytometry (CyTEK) panel that incorporated hallmark markers for all major immune populations as described previously ( 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…The primary mechanism through which Treg cells control inflammatory T cells is through the production of adenosine, which interacts with the adenosine receptor, specifically, A 2A. This receptor is predominately present on inflammatory T cells and inhibits their differentiation [ 80 ].…”
Section: Discussionmentioning
confidence: 99%